Synthesis of new pyrazoles as anti-inflammatory agents - Shimaa Magdy Ibrahim Alhamaky; Ashraf Fouad Zaher; Lamia Wagdy Mohamed; Mohamed Abdelrahman Shaaban (Cairo : Shimaa Magdy Ibrahim Alhamaky, 2018)
This thesis includes four chapters in addition to references and arabic summary. The first chapter is the introduction, which consist of a brief literature survey of the synthesis and reactions of pyrazoles. It also involve an account on the anti-inflammatory agents. The second chapter involves the objectives of this work based on structure activity relationship and molecular modelling study. It also demonstrates the schemes of synthesis of the new derivatives. The third chapter clarifies the theoretical discussion of the experimental work used to synthesis in addition to spectroscopic data of the starting materials I , II and the target new compounds IIIa-f, IVa-L, Va-f. The fourth chapter is divided in to three parts representing the experimental part of the thesis. The first part is the synthetic approach that comprises the detailed methods for preparation of designed compounds in three schemes. Scheme I : includes synthesis of I followed by reaction with o-fluoro aniline affording derivative II. This was followed by coupling with diazotized aromatic amines in ethanol in presence of sodium acetate to afford IIIa-f. Scheme II : involves the mannich procedure for the reaction of IIIa-f with anilin or 2,6-dimethyl aniline and 40% formaldehyde in ethanol at 60 oC to afford IVa-L. Scheme III: involves the synthesis of Va-f by cyclization reaction of II with appropriate aromatic aldehydes and malononitrl in ethanol containing ammonium acetate
Thesis (M.Sc.) - Cairo University - Faculty of Pharmacy - Department of Organic Chemistry
Issued also as CD
Keywords: Mannich reaction; Pyrazoles; Pyrazolopyridine